Uttarakhand Third Five-Year Plan Progress Report 1964-65 (Second Quarter July - September) - Planning Commission (Planning Commission, 1964)
The Uttarakhand Third Five-Year Plan Progress Report for the second quarter of 1964-65 provides a detailed overview of developmental initiatives across key sectors in the region. Horticulture achievements included the establishment of 12 model orchards, production of over 18,000 fruit plants, distribution of vegetable seeds, and significant honey and fruit sales, supported by effective plant protection teams. Animal husbandry development featured veterinary services treating over 27,000 animals, breeding programs generating more than 500 progeny, and financial support for local livestock initiatives. Community development efforts focused on improved agricultural practices, distribution of 880 tons of fertilizer, establishment of 1,058 compost pits, and the promotion of women’s training programs. Power development advanced with ongoing projects in Pithoragarh, Uttarkashi, and Chamoli, enhancing local electricity access. Education initiatives included the opening of 50 new primary schools and expansion of degree college curricula. Drinking water and sanitation projects improved access in towns and villages, while medical and public health programs treated over 21,000 outpatients and implemented tuberculosis, eye care, and first-aid campaigns. Government expenditure reached approximately Rs. 1.02 crores, reflecting a strong commitment to the Plan’s objectives. Overall, the report demonstrates significant progress in promoting socio-economic development, infrastructure expansion, and community well-being in Uttarakhand.
Uttar Pradesh
Uttar Pradesh
Keywords: Uttarakhand Development; Third Five-Year Plan; Horticulture Expansion; Animal Husbandry; Community Development; Power Projects; Primary Education; Drinking Water Supply; Public Health; Veterinary Services; Women’s Initiatives; Agricultural Support